IMPORTANCE OF SITUATIONAL TASKS IN PREPARATION OF A WOULD-BE DOCTOR OF GENERAL PRACTICE - Климанский, Руслан; Касрашвили, Григорий; Самойленко, Елена (SWorldJournal, 2021)
Nowadays the problem of preparation of a general practitioner is one of the most important in modern medical education. The article outlines the place of surgery in this process and describes some ways to make teaching surgery more effective. Therefore, t